2019
DOI: 10.3390/min9020093
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element and Stable Isotope Geochemistry of Lwamondo and Zebediela Kaolins, Limpopo Province, South Africa: Implication for Paleoenvironmental Reconstruction

Abstract: The aim of the present study was the paleoenvironmental reconstruction of the prevailing environment under which the Lwamondo and Zebediela kaolin deposits were formed. Hence, this study reports deuterium and oxygen stable isotope values and trace and rare earth element concentrations for two samples of kaolin. Upper continental crust-normalised trace-element patterns reveal that large ion lithophile elements and high-field-strength elements are generally depleted in Lwamondo and Zebediela kaolins, whereas tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…However, according to the Köppen-Geiger climate classification, Limpopo Province, where the studied kaolins are found, has an arid steppe hot climate characterised by temperatures above 18°C [43,44]. Previous estimation of the temperature of kaolinisation of studied kaolins showed that the Lwamondo Kaolin formed under temperatures of 26.9 ± 3.6°C, whereas the Zebediela Kaolin formed under temperatures of 36.6 ± 4.2°C [22]. This suggests that in the area, there has been a climatic change from humid when the kaolins formed to arid steppe currently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, according to the Köppen-Geiger climate classification, Limpopo Province, where the studied kaolins are found, has an arid steppe hot climate characterised by temperatures above 18°C [43,44]. Previous estimation of the temperature of kaolinisation of studied kaolins showed that the Lwamondo Kaolin formed under temperatures of 26.9 ± 3.6°C, whereas the Zebediela Kaolin formed under temperatures of 36.6 ± 4.2°C [22]. This suggests that in the area, there has been a climatic change from humid when the kaolins formed to arid steppe currently.…”
Section: Discussionmentioning
confidence: 99%
“…Lwamondo and Zebediela kaolins are in Thulamela and Lepelle-Nkumpi Municipalities in Limpopo Province, South Africa. The geology of Lwamondo and Zebediela areas has been detailed in Raphalalani et al [22]. Lwamondo is mainly dominated by rocks of the Proterozoic Soutpansberg Group [23], whereas Zebediela is made up of rocks of the Proterozoic to Jurassic Transvaal Group [24,25].…”
Section: Geology Of the Areamentioning
confidence: 99%